2016
DOI: 10.3141/2559-10
|View full text |Cite
|
Sign up to set email alerts
|

Parking Sensing and Information System: Sensors, Deployment, and Evaluation

Abstract: Abstract. This paper describes a smart parking sensing and information system that disseminates the parking availability information for public users in a cost-effective and efficient manner. The hardware framework of the system is built on advanced wireless sensor networks and cloud service over the Internet, and the system is highly scalable. The parking information provided to the users is set in the form of occupancy rates and expected cruising time. Both are obtained from our analytical algorithm processi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Correa et al suggested the cooperation of autonomous vehicles within a vehicular sensor network (VSN) [19]. Other examples of the use of WSN can be found in [20] and [21]. In short, there are a few parking systems where sensors are used to determine spots.…”
Section: Related Workmentioning
confidence: 99%
“…Correa et al suggested the cooperation of autonomous vehicles within a vehicular sensor network (VSN) [19]. Other examples of the use of WSN can be found in [20] and [21]. In short, there are a few parking systems where sensors are used to determine spots.…”
Section: Related Workmentioning
confidence: 99%
“…Correspondingly, we set the 25000 EVs in our simulation ( 25000 ≈ 580000 × 0.48 × (1.648/17.914) ). The vehicle travel pattern is simulated according to the typical travel behavior of home-to-work commuters [11], [12]. These studies show that typical arrival times at workplaces ranges from 7am-10am.…”
Section: Experiments Datamentioning
confidence: 99%